Pengaruh Media Game Edukasi Berbasis Educandy Dalam Meningkatkan Penguasaan Mufradat Peserta Didik Kelas V MIN 2 Kota Surabaya - Rahayu, Afiyah Wildah; Taufik, Taufik; Chasanah, Uswatun; Munawir, Munawir (IBTIDA-Jurnal Kajian Pendidikan Dasar, 2024)
The research was motivated by the problem of learning Arabic which tends to be monotonous, thus affecting learning motivation and students' ability to remember vocabulary (mufradat). The aim of this research is to identify the effect of using educational game media based on the Educandy application on increasing the mastery of mufradat for class V students at MIN 2 Surabaya City. The research uses quantitative methods with a quasi-experimental design with a nonequivalent group design model. The VC class as an experimental group uses educational game media, while the VA class as a control group uses conventional methods. Multiple choice tests were applied to the pretest and posttest to measure the increase in mufradat mastery. Data analysis was carried out through validity, reliability, descriptive statistics, normality, homogeneity and t-test tests. The research results showed that the average pretest score in the experimental class was 47.75, while in the control class it was 44.25. In the posttest, the average of the experimental class increased to 71.00, while the control class became 61.63. The t-test proved a significant difference between the two classes, showing that the use of educational game media had a significant effect in increasing students' mastery of mufradat.